Structure and steroid isomerase activity of Drosophila glutathione transferase E14 essential for ecdysteroid biosynthesis. Issue 7 (9th January 2020) - Škerlová, Jana; Lindström, Helena; Gonis, Elodie; Sjödin, Birgitta; Neiers, Fabrice; Stenmark, Pål; Mannervik, Bengt
Abstract : Ecdysteroids are critically important for the formation of the insect exoskeleton. Cholesterol is a precursor of ecdysone and its active form 20‐hydroxyecdysone, but some steps in the ecdysteroid biosynthesis pathway remain unknown. An essential requirement of glutathione (GSH) transferase GSTE14 in ecdysteroid biosynthesis has been established in Drosophila melanogaster, but its function is entirely unknown. Here, we have determined the crystal structure of GSTE14 in complex with GSH and investigated the kinetic properties of GSTE14 with alternative substrates. GSTE14 has high‐ranking steroid double‐bond isomerase activity, albeit 50‐fold lower than the most efficient mammalian GSTs. Corresponding steroid isomerizations are unknown in insects, and their exact physiological role remains to be shown. Nonetheless, the essential enzyme GSTE14 is here demonstrated to be catalytically competent and have a steroid‐binding site. Abstract :